Agritourism in Central Luzon, Philippines: Status, Challenges, and Pathways to Sustainable Growth - Alar, Sherwin S. (Philippine Social Science Journal, 2024)
This study explores the status, challenges, and pathways to sustainable growth in Central Luzon, Philippines agritourism. Data from agritourism trainers, farm owners, trainees, and stakeholders are analyzed using a descriptive research design and statistical tools such as Multivariate Tests, Wilks’ Lambda (Exact Statistic), and Spearman’s Rank-Order Correlation. The research identifies significant variations in agritourism status across site characteristics and underscores the importance of tailored management approaches. Moreover, it reveals a positive correlation between knowledge acquisition and utilization, emphasizing the role of training in enhancing agritourism practices. Despite challenges like waste management and bureaucratic hurdles, agritourism is recognized as a valuable driver of economic development in Central Luzon, offering opportunities for rural communities and sustainable agriculture. This study’s implications inform policymakers, educators, and government officials, providing insights for agritourism program development and policy formulation, ultimately contributing to regional economic growth and community well-being.